Performance improvement of local automotive industry by adopting JMM - Mohiuddin, A. K. M.; Julia , Abdul Jabar (2015)
In the era of globalization, most companies all over the world are constantly looking for ways to increase productivity and at the same time to remain competitive to reduce cost. Companies in automotive manufacturing industry are no exceptions. Substantial evidence suggests that practices associated with Japanese Manufacturing Management (JMM) can yield a superior competitive advantage in terms of productivity, quality and provide overall successful business performance. This paper discusses the transfer of the best practice of the JMM locally and obtain the impact of the adoption and adaptation of the JMM in a Malaysian automotive company. An in-depth case study was conducted to identify what are the changes in terms of the philosophy and practices undertaken by the automotive company and ascertain the impact of the JMM on its manufacturing and financial performances. The elements of business performance from the viewpoint of manufacturing based on safety, quality, cost and delivery were quantified and examined. These elements are safety, Parts per Million (PPM), in-line Defect per Unit (DPU), First Time Quality (FTQ), cycle time, productivity, efficiency and stock level. The results show a positive impact to the automotive plant manufacturing performance. For example, safety index has reduced to 0 major accident occurrences. The PPM and In-line DPU have improved by 98% and 91% respectively. The FTQ has improved by 167% and cycle time was reduced from 20 minutes to 6 minutes. The productivity has increased up to 43% whilst the efficiency was at 99.9%. The stock level was reduced from half month to 3 days after the adoption of the JMM. The results of the financial performance also show the profitability of the plant.